2019
DOI: 10.1088/1755-1315/329/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

A parametric analysis of the influence of wind speed and direction on the thermal comfort performance of a Passive Downdraught Evaporative Cooling (PDEC) system – field measurements from a Saudi Arabian library

Abstract: Building energy consumption in the desert climate of Saudi Arabia is dominated by cooling demand. Electricity for this cooling is generated predominantly from finite fossil fuel reserves. To improve resource efficiency and decrease carbon emissions, reducing this demand by using more passive cooling approaches is desirable. One system is the passive downdraught evaporative cooling (PDEC) tower. PDEC captures hot, dry winds at the top of a tower and then cools the air by passing it through or over water. This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The lower panel shows the WBT calculated from ERA5. In situ measurements of WBTs recorded a summer average of 18.8 • C [30]. We can see that the derived WBT here is slightly lower, probably due to the grid size (31 km), and is of 17 nights.…”
Section: Riyadhmentioning
confidence: 60%
“…The lower panel shows the WBT calculated from ERA5. In situ measurements of WBTs recorded a summer average of 18.8 • C [30]. We can see that the derived WBT here is slightly lower, probably due to the grid size (31 km), and is of 17 nights.…”
Section: Riyadhmentioning
confidence: 60%
“…A case study in Thailand's hot and humid climate suggested that indoor temperature decreased by between 2 and 6.2 • C in a wooden structure cell room that adopted a solar chimney with a dampened roof [78]. For the very hot and dry climate, the results measured at a Saudi Arabian library, which utilized two cooling towers that contain wet pads, showed a significant passive cooling effect, as the indoor air temperature was cooled to 25.8 • C when the outdoor dry bulb temperature was 46 • C [79].…”
Section: Passive Cooling Methodsmentioning
confidence: 99%